Determinants of Farmers' Participation in Banana Insurance in Chitwan District, Nepal (Journal of Agriculture and Environment, 2022)
This study was conducted to identify the factors affecting the adoption of banana insurance in Chitwan district of Nepal. A total of 160 samples (80 insurers and 80 non-insurers of banana producers) were selected randomly to collect primary data. Primary data were collected by conducting household survey using personal interview method in the month of September 2019. The logit model was used to identify the factors affecting the adoption of banana insurance policy among farmers. The result showed that the explanatory variables, area under banana cultivation, membership to cooperatives, and awareness about the agriculture insurance, perception of farmer about the necessity of crop insurance, agriculture extension services, and age of banana orchard were significantly contributing to the adoption of banana insurance policy. It also revealed that organization of awareness program, mobilization of groups and cooperatives were the important tools to promote banana insurance program. The findings would be helpful to make the insurance program more effective and hence increase the adoption of insurance policy and ultimately benefit farmers by enhancing their ability to manage risks in agriculture.